Fieldwork for social research : a student's guide - Phillips, Richard; Johns, Jennifer (Thousand Oaks : SAGE Publications, 2024)
"This books is a step-by-step introduction to successful fieldwork, this guide will help students plan, design, conduct and share their research. It is packed with tools and real-world examples"--
Keywords: Social sciences -- Research -- Methodolgy; Social sciences -- Fieldwork